A scalability-centric perspective on global human development within environmental limits - Soumyajit Bhar; Chirag Dhara (Sustainability: Science, Practice, & Policy)
The Human Development Index (HDI) positions Global North countries as development benchmarks, overlooking their high environmental footprints. This perspective poses a dilemma: global adoption of Northern lifestyles risks surpassing planetary biophysical limits, while non-adoption risks perpetuating developmental inequality. The Planetary Pressures adjusted-HDI (PHDI) from the United Nations Development Program (UNDP)’s 2020 Report aimed to incorporate environmental pressures into the assessment of human development. However, countries ranking highest on the PHDI also exhibit considerable environmental footprints, limiting the PHDI’s utility as a sustainability metric. Our study introduces a revised metric emphasizing “scalability” as a pivotal facet of sustainability. Scalability, in our context, refers to the theoretical possibility of scaling a country’s historical developmental trajectory to the entire global population without exceeding planetary biophysical limits rendered in absolute terms. This emphasis on historicity and absolute environmental performance distinguishes our approach from the PHDI. Our results highlight Panama, Costa Rica, Sri Lanka, Peru, and Albania as having achieved high social progress with low environmental costs or high levels of scalable development. This signals that substantial social progress can be achieved globally without overstepping biophysical limits. Nonetheless, simple projections indicate that the environmental footprints of these countries may scale unsustainably in the future if current trends persist. This study underscores the continued need to prioritize scalability in the future and recommends shifting the narrative to countries that exemplify scalable development to provide strategic insights to the Global South.